Basic digital competences of university students before and during the COVID-19 pandemic - Burgos, Carmen; Jorquera, Ricardo; Aliaga, Verónica; López, Eloy (Frontiers in Education, 2023)
The objective of this study was to compare the digital competences of university students before and during the COVID-19 pandemic, and to determine the impact of internet use on these competences, specifically those related to social communication, collaborative learning, as well as information searching and processing. The sample comprised 415 Spanish students who began university studies between 2019 and 2022. The instrument used was the COBADI. The results indicate an increase in internet use to talk with friends in social networks and work with classmates, such as in collaborative homework. In terms of digital competences during the pandemic, there was an increase in competences related to social communication, collaborative learning, and information searching and processing. The study also found that academic and recreational internet use predicted basic digital competences, as determined by a MANCOVA analysis. The role of the pandemic context in increasing basic digital competences in university students is discussed.